MEMPERBAIKI CARA BELAJAR SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI MADRASAH ALIYAH LABORATORIUM UIN-SU MEDAN - Winida Sari (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
This study aims to get a clear picture of improving the way students learn through group guidance services at Madrasah Aliyah UIN-SU Medan Laboratory. As for the informants in this study were tutors, students and subject teachers. This type of research is qualitative, namely research that seeks to find facts and describe the research findings. The results of the study can be stated that the implementation of the Guidance Service Group given to students is to provide knowledge and understanding of good learning methods and ways of learning that are not good. Students reflect actions and do positive learning methods. Guidance Services Groups play a role in providing students with an understanding of how to improve student learning. Guidance Services The group provided helps students understand themselves, students are able to understand actions, including the ability to improve their learning methods well. Then the researchers concluded that after BKp services were conducted, student learning methods became more effective than usual.Keywords: Learning Methods and Guidance Groups